A novel host restriction factor MRPS6 mediates the inhibition of PDCoV infection in HIEC-6 cells - Jiang, Yuhang; Zhang, Guoqing; Li, Letian; Chen, Jing; Hao, Pengfei; Gao, Zihan; Hao, Jiayi; Xu, Zhiqiang; Wang, Maopeng; Li, Chang; Jin, Ningyi (Frontiers in Immunology, 2024)
Introduction Porcine deltacoronavirus (PDCoV) is a zoonotic pathogen with a global distribution, capable of infecting both pigs and humans. To mitigate the risk of cross-species transmission and potential outbreaks, it is crucial to characterize novel antiviral genes, particularly those from human hosts. Methods This research used HIEC-6 to investigate PDCoV infection. HIEC-6 cells were infected with PDCoV. Samples were collected 48 h postinfection for proteomic analysis. Results We discovered differential expression of MRPS6 gene at 48 h postinfection with PDCoV in HIEC-6 cells. The gene expression initially increased but then decreased. To further explore the role of MRPS6 in PDCoV infection, we conducted experiments involving the overexpression and knockdown of this gene in HIEC-6 and Caco2 cells, respectively. Our findings revealed that overexpression of MRPS6 significantly inhibited PDCoV infection in HIEC-6 cells, while knockdown of MRPS6 in Caco2 cells led to a significant increase of virus titer. Furthermore, we investigated the correlation between PDCoV infection and the expression of MRPS6. Subsequent investigations demonstrated that MRPS6 exerted an augmentative effect on the production of IFN-β through interferon pathway activation, consequently impeding the progression of PDCoV infection in cellular systems. In conclusion, this study utilized proteomic analysis to investigate the differential protein expression in PDCoV-infected HIEC-6 cells, providing evidence for the first time that the MRPS6 gene plays a restrictive role in PDCoV virus infection. Discussion Our findings initially provide the validation of MRPS6 as an upstream component of IFN-β pathway, in the promotion of IRF3, IRF7, STAT1, STAT2 and IFN-β production of HIEC-6 via dual-activation from interferon pathway.